Mobile laser scanning elevation data accuracy in closed and partially open sky area - Annok, Gerly; Tammin, Valdar; Liba, Natalja (Geodesy and Cartography, 2021)
Mobile laser scanning is being used more often in Estonia and abroad to obtain geospatial information. As the system is still new and being upgraded, different methods are being used to find out how accurately the mobile laser scanner can measure in different conditions. In this article the mobile laser scanner accuracy is being examined depending on surrounding environment and the importance of postprocessing. Mobile laser scanning elevation data accuracy obtained in difficult conditions is being assessed. Difficult conditions are considered locations where there are tall objects that interrupt the satellite signals’ trajectory to the receiver. To determine the elevation accuracy of mobile laser scanner data, coordinates with the raw broadcast and final ephemerides with the combination of the GNSS receivers’ data that were installed in ideal and not ideal environmental conditions were computed. As a result of the study, the error of the elevation data in the first polygon, situated in difficult conditions was 7 mm when the Kunda reference station data was used with raw broadcast and final ephemerides. Error in the second polygon was accordingly 17 mm and 19 mm. When calculations were conducted using raw broadcast ephemerides in a base station in an imperfect environment, the error in the first polygon was 103 mm and in the second 75 mm. When the precise ephemerides were added to base station data, the error in the first polygon was 6 mm and in the second 21 mm. From the study results, it could be concluded that the mobile laser scanning system measures within 2 cm accuracy even in a complicated environment.